Anti-hepatitis a virus seroprev alence among chronic viral hepatitis B and C HUSM and its association with Cyp3a4*18 polymorhism - Noraizal, Che Hamzah (Pusat Pengajian Sains Perubatan, 2012)
CYP3A4 is the major cytochrome in humans which shows reduced activity in chronic liver disease as well as in hepatic cirrhosis. The detection of this polymorphism may give an indication on the prognosis of patients having chronic viral hepatitis with superimposed hepatitis A infection. The aim of this study is to correlate the seroprevalence of anti-HAV antibodies in chronic liver disease patients having CYP3A4*18 polymorphisms. Methodology: This is a prospective study where patients' (n=ll9) blood was tested for anti-HAVlgG and CYP3A4* 18 polymorphism. Results: The overall anti-HAV seroprevalence was 88.2%. The etiology of CLD was hepatitis B in 96 patients (80.7%) and hepatitis C in 23 patients (19.3%). There was a significant increase in the age of the prevalence of this disease after 30 years of age (p=0.008). CYP3A4* 18 polymorphism was detected in 3 (2.5%) of the patients with chronic liver disease. However, there was no significant association between CP3A4*18 mutation and anti-HAV serology. Conclusions: Age was the most important factor in determining anti-HAV positivity. It is concluded that CYP3A4*18 genetic polymorphism does not play a main role in influencing the seroprevalence of anti-hepatitis A among chronic viral hepatitis B and C liver disease patients.